Experimentos demonstrativos para o estudo do eletromagnetismo. - Monteiro, Hudson Roberto (2018)
Science is fundamental for our existence. Physics is among the subjects upon which science is based. Besides being of extreme importance in the understanding of concepts related to the existence of human beings and on laws that govern the universe, it can also contribute to a civic awareness education through a teaching method oriented to students' daily situations. Unfortunately, there is a shortage of experimental practice on physical and natural sciences in Brazil, with excessive dependence on course material, expository method, number of classes reduced and teachers’ insufficient qualification. Given these circumstances, this thesis was idealized as a proposal to facilitate students learning concerning electromagnetism and Maxwell's laws. Therefore, a manual for the construction of electromagnetism experiments was devised and applied, in 2017, to a group of senior high school students at a public school located in the State of São Paulo. That aimed to develop students’ motivation regarding science studying tied to investigative experimentation. The activities were conducted for about eighteen weeks and involved preparation, elaboration, presentation in class with discussion, and final presentation to the community of the projects selected by students with the teacher's orientation. Concurrently, the teacher presented concepts related to the experiments investigated by the students. The utilization of the class content done with the proposed method comparing to the traditional method was analyzed from the number of correct answer rates in tests. The results of the 2016 class – control group – were compared to the 2017 class – experimental group. The 2016 class had a 41,2 % of correct answers rate whereas the 2017 class had a 50,9% which suggests the practice allowed for better students’ performance.